Printing for profit : the commercial publishers of Jianyang, Fujian (11th-17th centuries) - Chia, Lucille (Harvard-Yenching Institute monograph series, 2002)
Based on an extensive study of Jianyang imprints, genealogies of the leading families of printers, local histories, documents and annotated catalogues and bibliographies, this is not just a history of commercial printing but also a wide-ranging study of the culture of the book in traditional China.